Міжнародний досвід післявоєнного розвитку економіки: уроки для України - Дідик, А. М.; Погорелов, Ю. С.; Didyk, A. M.; Pogorelov, Y. S. (Видавництво Львівської політехніки, 2023)
Оцінено розмір збитків для української економіки за 2022 р. внаслідок військових дій. Здійснено аналіз міжнародного досвіду післявоєнного розвитку економік країн, постраждалих від воєнних дій, зокрема Німеччини, Італії, Південної Кореї, Японії. Виділено драйвери та заходи післявоєнного економічного розвитку для окремих країн, постраждалих від воєнних дій. Узагальнено чинники успіху післявоєнного розвитку економік, постраждалих від воєнних дій, та на підставі такого узагальнення запропоновано чинники успіху для післявоєнного розвитку української економіки.

The article is devoted to issues of developing Ukrainian economy after the war. Damage for Ukrainian economy in 2022 after the aggression of the russian federation in 2022 is enormous. Economic consequences of aggression of the russian federation for Ukraine are comparable to consequences for other countries in XX century after the wars. This fact causes the expediency of studying and using experience on the mentioned countries concerning development of their postwar economies. There is an experience of the postwar economic development of Southern Korea, Germany, Italy and Japan analyzed in the article. A special attention is devoted to Marshall Plan and Morgenthau Plan. It is shown that, from the one point of view, actions and drivers of postwar economic developing were similar for different countries. From the other point of view, all even similar actions and drivers of postwar economic developing took into account the specific features of economic situation and national mentality in every country. Analyzing postwar economic development of some countries allowed specifying the general factors of successful postwar economic development. Such factors include the specified plan of actions, recovering the damaged infrastructure of the national economy, the large-scale investing and financial support, grants, industrialization of economy and accent on highly technological industries, time-bounded character of planned actions, making the necessary institutions or their massive involvement (in case if they exist), defining all the participants of the planned actions, systematic and consistent character of the planned actions, making the export-oriented economy, partnership between large businesses and a State, combining the tools of market-oriented economy and centralized state planning.
The international experience of postwar economy development: the lessons for Ukraine
Keywords: втрати; післявоєнний розвиток економіки; план Маршалла; план Моргентау; аналіз; драйвер; чинник; damage; postwar economy’s development; Marshall Plan; Morgenthau Plan; analysis; driver; factor; 338.1; 330.5; 338.23